Polymer‐Based Therapeutic Nanoagents for Photothermal‐Enhanced Combination Cancer Therapy. Issue 11 (30th September 2021) - Yang, Nan; Cao, Changyu; Li, Hui; Hong, Ying; Cai, Yu; Song, Xuejiao; Wang, Wenjun; Mou, Xiaozhou; Dong, Xiaochen
Abstract : Significant efforts have been made on cancer control by scientists. And various methods for cancer treatment are constantly emerging. Among them, photothermal therapy (PTT) has received a wide range of attention due to its special features, including noninvasiveness, remote control, high selectivity, negligible drug resistance, insignificant side effects, and desired therapeutic effects. Photothermal agents (PTAs), which can convert light into heat under laser irradiation, serve as a crucial role during PTT for killing cancer cells. In the past decades, different kinds of PTAs have been successfully developed. Among these, polymer‐based PTAs are widely used in cancer diagnosis and PTT owing to their competitive features, including customizable designs, controllable synthesis, excellent biocompatibility, negligible cytotoxicity, satisfactory photostability, and desirable photothermal effects. In addition, along with PTT, they also play a crucial role in tumor targeting, cancer imaging, drug delivery, and combination therapies. Herein, the recent advances in cancer therapeutic nanoplatforms built on polymers are reviewed in detail. Meanwhile, future opportunities and challenges for polymer‐based PTAs in cancer therapy are also exemplified. Abstract : This review aims to improve the reference for the subsequent design of multimodal photothermal platforms based on polymers in the future. This review also elaborates on the opportunities and challenges for the future development of polymer‐based photothermal therapy (PTT)‐enhanced cancer combination therapy.